Comparison of Alpha-Blocker Monotherapy Versus Combination Therapy in Moderate to Severe LUTS: A Real-World Study - Muhammad Haroon Ghous, Umer Saeed, Mudassara Saqib, Maliha Karim, Farooq Sultan, Muhammad Nouman Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Lower urinary tract symptoms (LUTS) in men significantly impair quality of life and arecommonly managed using α-blockers as first-line therapy, with or without the addition of 5αreductase inhibitors (5-ARIs). This real-world, prospective comparative study evaluated the effectiveness of α-blocker monotherapy versus α-blocker plus